2020
DOI: 10.1016/j.ijid.2020.07.069
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 response in low- and middle-income countries: Don’t overlook the role of mobile phone communication

Abstract: Highlights The response to the COVID-19 pandemic in low- and middle-income countries is challenged by fragile health systems and poverty. Expanded access to mobile phones will facilitate their use in the COVID-19 response. Mobile phone technology can improve case-reporting and patient referral pathways. We give examples of initiatives enhancing patient care and public health outcomes. We present a checklist for helpful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 24 publications
(32 reference statements)
3
28
0
Order By: Relevance
“…This is supported by Meadows who outlines information flows and their structure as an effective leverage point, with missing feedback identified as one of the most common causes of system failure (Meadows, 2008; Stanton & Harvey, 2017). Indeed, clarity of reporting and communication have been identified as an issue limiting the effectiveness of the response to COVID‐19 (Verhagen et al, 2020). Further, risk awareness at the community level has been labeled as one of the most effective ways to slow or prevent transmission of COVID‐19 (Chatterjee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Meadows who outlines information flows and their structure as an effective leverage point, with missing feedback identified as one of the most common causes of system failure (Meadows, 2008; Stanton & Harvey, 2017). Indeed, clarity of reporting and communication have been identified as an issue limiting the effectiveness of the response to COVID‐19 (Verhagen et al, 2020). Further, risk awareness at the community level has been labeled as one of the most effective ways to slow or prevent transmission of COVID‐19 (Chatterjee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…104,[206][207][208][209][210][211] It has been reported that COVID-19 has been a neglected issue in LMICs. 212,213 Internationally, eight of the ten nations with the highest numbers of new cases of COVID-19 are upper middle income (Peru, Russia, South Africa, Argentina, Colombia, Mexico, Brazil) or lowermiddle-income states (India). 212 It has been reported that in compassion to high-income countries (HICs), CCP transfusions have received scant attention in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“… 212 It has been reported that in compassion to high-income countries (HICs), CCP transfusions have received scant attention in LMICs. 213 Multiple reasons have been identified as the systemic challenges of resource-poor settings. Several LMICs do not possess a safe and reliable blood transfusion facility; this situation existed before COVID-19 due to poor donor enlistment and deployment, collections process, distribution, lack of infectious testing capability, and transfusion itself.…”
Section: Discussionmentioning
confidence: 99%
“…LMICs, even on a good day, are resource deficient and certainly not prepared to deal with a healthcare crisis of this magnitude despite a lower disease burden of COVID-19 infections [ 5 ]. Though the healthcare community, and specifically leading oncologic societies such as the American Society of Clinical Oncology (ASCO) and the European Society of Medical Oncology (ESMO), put together triaging recommendations to best utilize resources without compromising care, these guidelines are not applicable to all LMICs, as each country struggles with its unique challenges.…”
Section: Introductionmentioning
confidence: 99%